2010
DOI: 10.1186/1471-2407-10-158
|View full text |Cite
|
Sign up to set email alerts
|

Serum tartrate-resistant acid phosphatase 5b activity as a prognostic marker of survival in breast cancer with bone metastasis

Abstract: BackgroundSerum tartrate-resistant acid phosphatase 5b (TRACP 5b) activity is a marker of osteoclast number and is elevated in breast cancer (BC) patients with extensive bone metastasis, which might in turn reflect the tumour burden. We tested the hypothesis that baseline serum TRACP 5b activity and its interval change are potential prognostic markers of survival in BC patients with bone metastasis.MethodsWe analyzed the data from previous prospective studies. A total of 100 patients with newly diagnosed bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
0
15
1
3
Order By: Relevance
“…3 ACP5 expression has been shown to be significantly upregulated in breast and ovarian cancers and melanoma 4,5 and is a useful serum marker for extensive bone metastasis. [6][7][8][9][10] Recent studies have reported that ACP5 promotes the invasion and distal metastasis of melanoma and breast cancer cells through the modulation of focal adhesion kinase (FAK) phosphorylation. Additionally, ACP5 overexpression is indicative of the poor prognoses of human melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 ACP5 expression has been shown to be significantly upregulated in breast and ovarian cancers and melanoma 4,5 and is a useful serum marker for extensive bone metastasis. [6][7][8][9][10] Recent studies have reported that ACP5 promotes the invasion and distal metastasis of melanoma and breast cancer cells through the modulation of focal adhesion kinase (FAK) phosphorylation. Additionally, ACP5 overexpression is indicative of the poor prognoses of human melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study measured serum bone resorption markers at baseline and 6 months after treatment with Zoledronic acid, and used the level change of the markers (e.g., increase or decrease) after the treatments. Other reports had shown the value of TRACP‐5b in breast cancer and ICTP in nonsmall cell lung cancer for predicting survival, but another report could not document any prognostic value of pretreatment ICTP in patients with prostate cancer . A previous study of metastatic bone disease showed that percent changes of urine N‐terminal cross‐linking telopeptides of type I collagen (NTX) and serum ICTP were associated with disease progression in bone .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, researchers have identified more than a dozen proteins that may be considered biomarkers of bone metastasis in preclinical models of breast cancer and in human breast tumors (Table 1) [6-12]. Some of these biomarkers appear to be useful for monitoring bone metabolism in patients with various bone-related diseases, including osteoporosis, as well as monitoring patients receiving antiresorptive agents [13, 14].…”
Section: Introductionmentioning
confidence: 99%